Breeding of a new white-fleshed loquat cultivar Puhuabai - LIN Shoukai; TU Siping; MA Shiwei; LIN Zhicong; FAN Guofan; LIN Shunquan; WU Jincheng (Guoshu xuebao, 2025)
Puhuabai is a new mid-to-late season and white-fleshed loquat cultivar developed from the seedling populations at Jiuhua Farm in Putian City, Fujian Province. Its genetic lineage was verified through molecular marker analysis. An exceptional loquat seedling tree was discovered in the 1980s near the cattle pen at Yanghu Headquarters of Jiuhua Farm (a state-owned farm established in 1955). This tree exhibited stable fruiting performance, yellowish-white flesh, and superior quality. From 1984 to 1996, graft propagation trials in multiple locations (e.g., Xiazheng, Longqiao Yangxi, Xiuyu District, Dayang Keshan, and Yuanpu) revealed its stable traits, including large fruit size, excellent flavor, high yield, and good disease resistance, leading to its preliminary selection as an elite line. In 2020, Putian University initiated systematic breeding and temporarily named it Puhuabai. In June 2021, It was confirmed that this cultivar originated from the natural seedling populations of loquat at Jiuhua Farm. SSR molecular marker analysis of 50 loquat germplasms demonstrated its closest genetic relationship to Jiefangzhong. Multi-regional and production trials from 2021 to 2023 culminated in its official certification by the Fujian Provincial Committee for Non-Staple Crop Variety Certification in December 2024. The trees have semi-spreading canopy with vigorous growth, robust branches and sparse lenticels. The leaves are broad-elliptic (30.26 cm×9.79 cm), tomentose, and dark green, with wedge-shaped base, rounded serrations, prominent venation and persistent stipules. The flowers are bisexual, with white petals, 5 styles, 30 stamens, 2.13 cm in diameter, 13.95 cm in inflorescence and cold tolerance (normal flowering/fruiting at 4℃). The nearly round fruits exhibit yellowish-white peel and flesh with easy peelling feature. Key characteristics include an average fruit weight of 58.75 g, edible portion rate of 70.98%, and 4-5 seeds per fruit. The soluble solids content is 12.87%, total soluble sugars (glucose equivalent) content is 9.54%, and titratable acidity (citric acid equivalent) is 0.36%, contributing to its fine-textured flesh and well-balanced sweet-sour flavor. The fruits develop for about 140 days and mature from mid-late April to early May in Dayang Township, Hanjiang District, Putian City, Fujian Province. The trees demonstrate vigorous growth, strong resistance to leaf spot disease, and excellent productivity with stable yields. This cultivar is recommended for cultivation in Putian, Fujian Province, and climatically similar regions at low-to-medium elevations. Cultivation site selection includes well-drained and acidic soil (pH 5.5-6.5) with deep loamy layers, rich organic matters and gentle slopes (<20°). Planting density is 40-42 plants·666.7 m-2 (4.0 m×4.0 m spacing). Dig planting holes (0.8 m deep×1.0 m diameter), layer with bean stalks/weeds (2/3 depth), add decomposed manure, and backfill the holes. Optimal planting periods are mid-October (autumn) or February to March (spring). Rootstock can choose Jiefangzhong seedlings with robust root systems. Fertilization can be recommended as follows: Young trees: N-focused (N∶P2O5∶K2O=1∶0.5∶0.6), 4-6 applications/year; Bearing trees: to control nitrogen and increase potassium (N∶P2O5∶K2O=1∶0.5∶1), with 2-3 applications/year. Spring (fruit enlargement): Fast-acting fertilizer (N∶P2O5∶K2O=3∶2∶2.5), 25%-30% annual dose. Summer (post-harvest): Fast-acting fertilizer (N∶P2O5∶K2O=3∶2∶2.5)+organic manure, 45%-50% annual dose. Autumn (optional): Fast-acting fertilizer (N∶P2O5∶K2O=5∶2.5∶5)+organic manure, 25%-30% annual dose. Pruning includes to cut back the whip seedling below 0.7 m to promote low branching, and maintain 0.5 m interlayer spacing, with 3-4 primary branches per layer, and 2-3 secondary branches per primary branch. Post-harvest pruning focuses on removing weak/pest-damaged branches and cutting back leafless shoots. Fruit management include to thin fruits to 3-8 per cluster, and bag fruits with dual-layer “paper bag+foam net” to improve fruit appearance. Harvest should be done at 90% maturity.